Food allergen triggers are increased in children with the TSLP risk allele and eosinophilic esophagitis. Issue 3 (March 2018) - Fahey, Lisa M.; Chandramouleeswaran, Prasanna M.; Guan, Shaobo; Benitez, Alain J.; Furuta, Glenn T.; Aceves, Seema S.; Wang, Mei‐Lun; Liacouras, Chris A.; Muir, Amanda B.; Sleiman, Patrick MA; Hakonarson, Hakon; Spergel, Jonathan M.; et al.
Abstract : Objectives: : TSLP has been shown to be associated with eosinophilic esophagitis (EoE). Specifically, children with EoE often have the nucleotides AA or AG instead of GG at the single nucleotide polymorphism position RS3806932. Presently, the phenotypic characteristics in EoE children with the TSLP EoE risk allele are unknown. Methods: : A retrospective analysis was performed of all children with EoE who had TSLP genotyping at The Children's Hospital of Philadelphia from 2008–2014. EoE food allergen triggers, presence of atopic features, IgE mediated food allergy and skin prick testing results were reviewed. The number and type of EoE food allergen triggers were compared with genotype using chi‐square analysis. Primary cell cultures from EoE patients with or without the risk allele were stimulated with ovalbumin and TSLP secretion was measured by ELISA. Results: : Fifty three of 309 patients were found to have no copies of the TSLP risk allele, whereas 256 patients were found to have one or more copies of the risk allele. There was an increase in the number of patients with three or more EoE food allergens among those who were either homozygous or heterozygous for the risk allele compared to those without the risk allele ( P < 0.0001). This was independent of their atopic background. Primary cultures from patients homozygous for the risk allele had greater TSLP secretion than those isolated from heterozygous patients. Conclusions: : The TSLP risk allele is associated with having multiple EoE food allergen triggers. This novel EoE genotypic‐phenotypic correlation may guide future treatment for those with the TSLP risk allele.